2016
DOI: 10.14569/ijacsa.2016.070404
|View full text |Cite
|
Sign up to set email alerts
|

Network Attack Classification and Recognition Using HMM and Improved Evidence Theory

Abstract: Abstract-In this paper, a decision model of fusion classification based on HMM-DS is proposed, and the training and recognition methods of the model are given. As the pure HMM classifier can't have an ideal balance between each model with a strong ability to identify its target and the maximum difference between models. So in this paper, the results of HMM are integrated into the DS framework, and HMM provides state probabilities for DS. The output of each hidden Markov model is used as a body of evidence. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…1 The ASSERT architecture and its connection to external modules future actions. Past research works (Luo et al 2016) and (Bolzoni et al 2009) have suggested a similar concept and the need to integrate intrusion detection systems with attack classifiers.…”
Section: Background and Related Workmentioning
confidence: 99%
“…1 The ASSERT architecture and its connection to external modules future actions. Past research works (Luo et al 2016) and (Bolzoni et al 2009) have suggested a similar concept and the need to integrate intrusion detection systems with attack classifiers.…”
Section: Background and Related Workmentioning
confidence: 99%